SERO-EPIDEMIOLOGICAL STUDY OF ANAPLASMA MARGINALE AMONG CATTLE - F. A. Atif; M. S. Khan; F. Muhammad; B. Ahmad (Journal of Animal and Plant Sciences, 2013)
The study was designed to determine the risk factors associated with seroprevalence of Anaplasma marginale among cattle in Sargodha, Khushab and Rawalpindi districts of the Punjab, Pakistan during September, 2009 to August, 2010. A total of 1050 serum samples were collected from selected small holders and private livestock farms using multistage cluster random sampling technique. The epidemiological data and relevant information regarding management, host and area determinants were collected on a questionnaire through interview. Antibodies against Anaplasma marginale were detected by MSP-5 competitive enzyme linked immunosorbent assay. Multivariate analysis of risk factors revealed that cattle of more than 4 year of age (OR=5.42), heavy tick infested (OR=2.10), crossbred (OR=1.59) cattle were significantly at higher risk for Anaplasma marginale. Use of Ivermectin (OR=16.50), moderate interval of acaricide frequency (OR=16.50), stall feeding (OR=8.30) and use of unhygienic needles (OR=24.00) at farms were significantly associated with seroprevalence to Anaplasma marginale in cattle (P<0.05). The Sargodha district was at higher risk (OR=1.81) for Anaplasma marginale infection as compared to Khushab and Rawalpindi districts. The study would help in the prevention and control of bovine anaplasmosis in Northern Punjab, Pakistan.
Keywords: Anaplasma marginale; seroprevalence; risk factors; cattle